Distributed finite‐time formation tracking control of multi‐agent systems via FTSMC approach. Issue 15 (1st October 2017) - Han, Tao; Guan, Zhi‐Hong; Liao, Rui‐Quan; Chen, Jie; Chi, Ming; He, Ding‐Xin
Abstract : This study investigates the finite‐time formation tracking control problem for multi‐agent systems. The objective is to control all the follower agents to converge into the desired formation in finite time while the geometric centre of the follower agents tracks the leader agent's trajectory in finite time simultaneously. Then, the distributed finite‐time formation tracking protocols are proposed via the fast terminal sliding mode control (FTSMC) scheme. On the basis of algebraic graph theory, properties of the Laplacian matrix and finite‐time stability theory, it is shown that the distributed formation tracking can be achieved in finite time under the proposed control protocol. Two numerical simulation examples are employed to illustrate the effectiveness of our theoretical results.